Clinical governance and continuous Quality Improvement in the veterinary profession: A mixed-method study - Ling, Tom; Doorly, Ashley; Gush, Chris; Hocking, Lucy (Veterinary Evidence, 2021)
96% of the veterinary profession agrees that Quality Improvement (QI) improves veterinary care. While clinical governance is an RCVS professional requirement, over the last year only 60% spent up to 3 days on the Quality Improvement activities which allow clinical governance to take place. 11% spent no time on it at all. A lack of time, know-how and organisational support were among the barriers preventing its adoption in practice. Rather than being an individual reaction to a problem, Quality Improvement is a formal approach to embedding a set of recognised practices, including clinical audit, significant event audit, guidelines and protocols, benchmarking and checklists. This framework should be applied within a just culture where errors are redefined as learning opportunities, and precedence is given to communication, team-work and team-morale, patient safety, and distributed leadership. Addressing this gap will require evolution – rather than a revolution. Persistent packages, given enough time and addressing the whole flow of the patient journey, trump one-off ‘heroic’ and narrowly-focused interventions. Creating a rhythm of learning alongside stability of practice allows lessons to be absorbed and improvements routinised. Doing good things well is better than doing perfect things sporadically and helps address the widespread concern that there is insufficient time for QI by making the time commitment more predictable and manageable. The research provides a robust, evidence-based, roadmap for the entire sector including professional organisations, educators, those in management positions and care providers.